Post‐Polymerization Strategy via Dual Site Clicking for Synthesizing Intrinsically Cross‐Linkable Semiconducting Polymers - Jaehoon Lee; Seungju Kang; Eunsoo Lee; Jiyun Lee; Tae Woong Yoon; Min‐Jae Kim; Yongjoon Cho; Mingfei Xiao; Yorrick Boeije; Wenjin Zhu; Changduk Yang; Jin‐Wook Lee; et al. (EcoMat)
ABSTRACT Crosslinked organic semiconductors have opened the way for various fabrication techniques in the field of organic electronics owing to their three‐dimensional network structure with high solvent resistivity. However, recent efforts to synthesize cross‐linkable semiconducting polymers have been limited by their low molecular weights and yields. In this study, this limitation is overcome by a novel post‐polymerization strategy. A reagent with a cross‐linkable functional group, (3‐mercaptopropyl)trimethoxysilane, is attached to a diketopyrrolopyrrole‐based donor–acceptor copolymer (DPPTT) via thioesterification and para‐fluoro‐thiol reaction, modifying two sites simultaneously. This modification preserves the molecular weight and electrical properties of the original polymers. In addition, the use of click chemistry enables high yield (98%) without any purification. The modified DPPTT demonstrated high resistance to organic solvents (80% retention dipped in 1‐chlorobenzene for 1 h). Exploiting this benefit, an ultrathin flexible array of 100 organic field‐effect transistors fabricated using conventional photolithography showed high‐performance reliability. Thus, this study provides a universal strategy to synthesize versatile polymer semiconductors for practical organic electronics.